The Reappearance of Racism: A Very Timely Issue - Basso, Pietro (Pontifícia Universidade Católica de São Paulo, 2015)
The reappearance and deepening of racism are analyzed from a perspective that is critical ofthe social foundations of that phenomenon in its four main aspects: class oppression, racialoppression, national oppression and sexual oppression. We discuss why the category race isstill full of significance and importance, not only to understand the roots, ideological componentsand practices of racism, but also for confronting racism with anti-racist struggles. Weproblematize the schematic distinction between old and new racism, as well as the nexusbetween racism and nationalism. In the center of the debate, we can find current questionslike the “ethnicization” of non-white peoples in peripheral countries, the criminalization ofimmigration, and the compression of workers’ salaries and rights.